Effect of alpha-lipoic acid supplementation on the lipid profile and lipid ratios in women with gestational diabetes mellitus: A clinical trial study - Hadise Aslfalah; Mehri Jamilian; Hadi Ansarihadipour; Mahdi Abdollahi; Ali Khosrowbeygi3comma (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Evidence suggests that Oxidative stress has been shown to plays an important role in gestational diabetes mellitus (GDM) etiology. On the other hand, women with GDM are at an increased risk for complications such as endothelial dysfunction and cardiovascular diseases. Objective: To investigate the effects of alpha-lipoic acid (ALA) on the maternal circulating values of lipid profile and lipid ratios in women with GDM. Materials and Methods: Sixty women with GDM were participated in the present study. The ALA group (n = 30) received ALA (100 mg/day) and the placebo group (n = 30) received cellulose acetate (100 mg/day) for eight wk. The maternal circulating values of hemoglobin A1C, triglyceride (TG), total cholesterol, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol, triglyceride-glucose (TyG) index, atherogenic index of plasma (AIP), non-HDL-C, and lipid ratios were assessed before and after the intervention. P-value < 0.05 was considered as statistically significant. Results: The values of TyG index (p < 0.001), TG (p = 0.006), TG/HDL-C (p = 0.003), and AIP (p = 0.005) decreased significantly in the ALA group after the intervention. Conclusion: Maternal circulating values of TyG index, TG, TG/HDL, AIP decreased after eight wk of ALA supplementation in women with GDM.